2001
DOI: 10.3758/bf03195761
|View full text |Cite
|
Sign up to set email alerts
|

Word reading and picture naming in Italian

Abstract: Results from two separate norming studies of lexical access in Italian were merged, permitting a comparison of word-reading and picture-naming latencies and the factors that predict each one for an overlapping subsample of 128 common nouns. Factor analysis of shared lexical predictors yielded four latent variables: a frequency factor, a semantic factor, a length factor, and a final factor dominated by frication on the initial phoneme. Age of acquisition (AoA) loaded highly on the first two factors, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
120
1
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 71 publications
(99 reference statements)
22
120
1
5
Order By: Relevance
“…effect, and one that is independent of the frequency effect (see Bates, Burani, D'Amico, & Barca, 2001, for a similar conclusion based on a factor analysis of Italian word reading and picture naming tasks). As long as the stimuli are words and the task involves a simple response to these words, there is a nearly perfect positive correlation between the magnitude of the frequency effect and the magnitude of the AoA effect over a whole range of tasks.…”
Section: Multitask Investigations Of the Locus Of The Aoa-effectmentioning
confidence: 58%
See 1 more Smart Citation
“…effect, and one that is independent of the frequency effect (see Bates, Burani, D'Amico, & Barca, 2001, for a similar conclusion based on a factor analysis of Italian word reading and picture naming tasks). As long as the stimuli are words and the task involves a simple response to these words, there is a nearly perfect positive correlation between the magnitude of the frequency effect and the magnitude of the AoA effect over a whole range of tasks.…”
Section: Multitask Investigations Of the Locus Of The Aoa-effectmentioning
confidence: 58%
“…This semantic hypothesis has been disfavoured for a long time, because Morrison et al (1992) failed to find an effect of AoA in a man-made vs. naturally-occurring (e.g., anchor vs. apple) decision task, whereas they found a huge AoA effect in a naming task with the same stimuli. Brysbaert et al (2000) In recent years, the semantic hypothesis has regained impetus, partly due to Brysbaert et al (2000;also see van Loon-Vervoorn, 1989;and Bates et al, 2001), partly due to the neuralnetwork account which predicts AoA effects for arbitrary mappings. As the relations between orthography and semantics are arbitrary (very few words that are orthographically similar also mean the same), the neural-network account predicts AoA effects over and above cumulative frequency effects for semantic tasks and verbal input.…”
Section: Interpretations Of the Frequency-independent Aoa Effectmentioning
confidence: 99%
“…In picture naming, however, the AoA-effect tends to be much larger than predicted on the basis of the frequency-effect (e.g. Barry, Hirsh, Johnston, & Williams, 2001;Bates, Burani, D'Amico, & Barca, 2001). …”
mentioning
confidence: 63%
“…We propose that the interaction of the effects of AoA and semantic context obtained in the present picture naming experiment arose because the selection of the lemmas of late acquired items was affected more strongly by the increased activation levels of extra-list competitors (many of which would be acquired earlier and would therefore be strong competitors) than the retrieval of the early acquired items. This account implies that the frequency-independent AoA effect observed in picture naming arises during lemma selection (Bates et al, 2001). …”
Section: Discussionmentioning
confidence: 96%
“…Although it could be argued that this parent report measure is simply another kind of subjective rating scale, the measure itself was based on diary and free-speech studies, and large numbers of validation studies have shown that the developmental effects detected by the CDI correlate highly with free speech and other forms of language behavior by children in the 8-30-month age range. Hence, we view the CDI as an objective measure of AoA, to complement the subjective ratings of AoA that have been used in other studies (for examples of how the contribution of these two AoA measures may differ for picture naming and reading, respectively, see Bates, Burani, D'Amico, & Barca, 2001).…”
Section: Methodsmentioning
confidence: 99%